2011
DOI: 10.1002/hbm.21313
|View full text |Cite
|
Sign up to set email alerts
|

Understanding specific effects of prenatal alcohol exposure on brain structure in young adults

Abstract: Prenatal alcohol exposure (PAE) is associated with various adverse effects on human brain and behavior. Recently, neuroimaging studies have begun to identify PAE effects on specific brain structures. Investigation of such specific PAE effects is important for understanding the teratogenic mechanism of PAE on human brain, which is critical for differentiating PAE from other disorders. In this structural MRI study with young adults, PAE effects on the volumes of automatically segmented cortical and sub-cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 49 publications
4
60
1
Order By: Relevance
“…Human and animal studies (Sulik et al, this volume) have documented both global and specific alterations in brain anatomy. For instance, alcohol exposure is often associated with smaller intracranial volume as well as volume deficits in specific brain regions over and above those accounted for by small intracranial volume (Archibald et al 2001;Chen et al 2011). Given this evidence of neurological and neurobehavioral impact, it is highly probable that functional neuroimaging, which enables observation and recording of brain activation in human samples, also will identify alterations associated with prenatal alcohol exposure whether or not accompanied by structural differences.…”
Section: Introductionmentioning
confidence: 99%
“…Human and animal studies (Sulik et al, this volume) have documented both global and specific alterations in brain anatomy. For instance, alcohol exposure is often associated with smaller intracranial volume as well as volume deficits in specific brain regions over and above those accounted for by small intracranial volume (Archibald et al 2001;Chen et al 2011). Given this evidence of neurological and neurobehavioral impact, it is highly probable that functional neuroimaging, which enables observation and recording of brain activation in human samples, also will identify alterations associated with prenatal alcohol exposure whether or not accompanied by structural differences.…”
Section: Introductionmentioning
confidence: 99%
“…Among pregnant women, the rate of any illicit drug use is 5.4% and has not changed significantly since 2010-2011 [12]. Use remains higher in younger women (14.6%, ages 18-25) compared to older women (3.2%, ages [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. A high proportion of women are using marijuana illegally and fail to disclose their use to their providers.…”
Section: Current Prevalence Estimates Of Prenatal Drug Exposurementioning
confidence: 99%
“…Prenatal alcohol is associated with overall reductions in global [38,39] and regional brain volume including the hippocampus, basal ganglia, cingulate cortex, and corpus callosum [37,[40][41][42][43]. Several studies indicate that reductions in brain volume linked to prenatal alcohol exposure were associated with deficits in cognitive function and facial dsymorphology.…”
Section: Maternal and Environmental Variablesmentioning
confidence: 99%
“…Chen et al, 2012;Lebel et al, 2012), deficits in various forms of learning and memory Lewis et al, 2015) as well as attentional and behavioural problems and psychiatric illnesses like depression (O'Connor et al, 2002;Roebuck et al, 1999). Exposure to ethanol intrauterine causes brain structural malformations e early exposure alters migration of neuronal and glial cells (Clarren et al, 1978) and animal studies have found that prenatal ethanol exposure reduced cell numbers in the limbic cortex (Museridze and Gegenava, 2010) and caused abnormal development of the hippocampus (Lobaugh et al, 1991).…”
Section: Fetal Alcohol Exposurementioning
confidence: 99%